The taxonomic status of the genus Moseria (Siphonophora, Physonectae) - Pugh, P. R. (Zootaxa, 2006)
The status of the two species presently included within the genus Moseri a (Siphonophora, Physonectae), M. c onvol uta (Moser, 1925) and M. sim ilis Margulis, 1977, is reviewed. Based on the availabil ity of new material, described herein, both are considered valid. They can be distinguished by the morphology of their bracts, tentill a and palpons. Whether there are di fferences in the nectophores re mains to be resolved. As the generic name Moseri a is pre-occupied for a ctenophore , a new generic name is required and Resomi a, gen. nov., is proposed. The systematic position of this genus within the physonect siphonophores is discussed in light of recent molecular phylogeny studies (Dunn et al. 2005b).